Prevalence of intimate partner violence and its coping strategies of women in Kaski district, Nepal. - Koirala,Iechha (2014)
ABSTRACT: Background :Intimate Partner Violence (IPV) is the most prevalent form of Gender Based Violence (GBV) worldwide, but also in Nepal. Experiencing intimate partner violence is considered a chronic and stressful life event. Traditional values, socio-cultural and social contexts influence the ways in which women cope with intimate partner violence. Despite myriad of adverse outcome, only limited studies have been undertaken in the context of intimate partner violence and women responses to the violence. So far until now, no studies have addressed expectations of battered women. Aims 1) To assess prevalence of physical, sexual and emotional violence by intimate partner in women aged 18-55 years in Kaski District, Nepal in the past one year. 2) To investigate coping strategies adopted by exposed women to overcome the violence. 3) To find out the expectation of battered women. Methods: A cross-sectional, population based household survey was carried out among 214 married women in selected areas in Kaski District, Nepal during the period September-December, 2014. The systematic sampling was carried out for the purpose of this study.We used the World Health Organization (WHO) multi-country study instrument and conducted interviews. Socio-demographic data were mainly presented by prevalence and their 95% Confidence Interval (CI). Results: The overall prevalence of physical, sexual and emotional violence by intimate partner in Kaski District, Nepal were 21%, 38% and 42% respectively. Majority of exposed women (35%) remain silent, they had not sought any help. Women reported various coping strategies one or more times; one or more strategies; depending upon the violent behaviors of their husbands and frequency of violence they faced, including 40% disappeared from the scene , 23% fought with husband, who exposed to physical violence. Under the emotional violence, 25% went to maternal home. Women who were exposed to sexual violence, 23% went to sleep with children. In order to minimize the violence, 34% women sought help for advocacy and 33% women would like to be aware about the availability of various services and legal assistances. Conclusion: Intimate partner violence is high among women in Kaski District, Nepal. In particular, women used different strategic responses, including remaining silent, protesting against violence, and seeking help from others. However, lack of shelter for the victims of partner violence, social-cultural norm and values, lack of aware of their right and existing law against violence and services women did not seek help. Understanding their coping strategies and expectation may give insight into how to further support to the women to minimise the violence in the society.